2021
DOI: 10.1007/s00417-021-05333-7
|View full text |Cite
|
Sign up to set email alerts
|

One-year outcomes of microhook trabeculotomy versus suture trabeculotomy ab interno

Abstract: Purpose To compare clinical success rates and reductions in intraocular pressure (IOP) and IOP-lowering medication use following suture trabeculotomy ab interno (S group) or microhook trabeculotomy (μ group). Methods This retrospective review collected data from S (n = 104, 122 eyes) and μ (n = 42, 47 eyes) groups who underwent treatment between June 1, 2016, and October 31, 2019, and had 12-month follow-up data including IOP, glaucoma medications, complic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…This flexibility is its most significant advantage. Yokoyama et al 28 compared trabeculotomy with TMH to GATT in a retrospective study, including 169 eyes (GATT 122 and TMH 47) and found that mean IOP at 12 months was generally similar between the groups (mid-teens) but with a slightly lower success rate for TMH (71% vs 62%; success defined as IOP between 5 mm Hg and 18 mm Hg and a ≥20% IOP reduction with no additional glaucoma surgery).…”
Section: Bypassing Trabecular Meshwork By Tissue Excision; Enhancing ...mentioning
confidence: 99%
“…This flexibility is its most significant advantage. Yokoyama et al 28 compared trabeculotomy with TMH to GATT in a retrospective study, including 169 eyes (GATT 122 and TMH 47) and found that mean IOP at 12 months was generally similar between the groups (mid-teens) but with a slightly lower success rate for TMH (71% vs 62%; success defined as IOP between 5 mm Hg and 18 mm Hg and a ≥20% IOP reduction with no additional glaucoma surgery).…”
Section: Bypassing Trabecular Meshwork By Tissue Excision; Enhancing ...mentioning
confidence: 99%
“…Mori et al, 13 Sato and Kawaji, 15 Hirabayashi et al, 16 Okada et al, 18 reported that there was no difference in the surgical effectiveness in the treatment of open angle glaucoma with regard to success rate, final IOP, or IOP reduction; these studies compared 180 degrees versus 360 degrees, one-quadrant versus two-quadrant, 120 degrees versus 180 degrees, and 120 degrees versus 360 degrees, respectively. In contrast, Yokoyama et al 17 found that 360 degrees suture trabeculotomy outperformed the sectoral microhook trabeculotomy. Qiao et al 14 reported that the reduction of IOP was greater in GATT than in KDB trabeculotomy.…”
mentioning
confidence: 91%
“…360-degree gonioscopy-assisted transluminal trabeculotomy (GATT) is used with the assistance of an iTrack system (iScience Interventional) 12 . Each of these procedures can lower IOP in POAG 13–18 . Published studies showed that there was a discrepancy in a different range of GT on the IOP-lowering effect and its safety.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Studies on cadaver eyes suggested that the extent of trabeculotomy incision influences IOP reduction [4]. While some studies reported varying IOP reduction efficacy based on the width of the surgical extent [5][6][7], others found no such differences [8][9][10][11][12][13]. Assessments of the correlation between surgical extent and IOP reduction efficacy often involved comparing different surgical procedures or groups with varying preoperative IOP or patient backgrounds [5][6][7]10,13].…”
Section: Introductionmentioning
confidence: 99%